CALPHAD modeling and experimental assessment of Ti-Al-Mn ternary system. (December 2018) - Liang, Zhi; Miao, Jiashi; Shi, Renhai; Williams, James C.; Luo, Alan A.
Abstract: There is an increasing need to develop lower cost titanium alloys. In this investigation, Ti-Al-Mn ternary alloy system was experimentally and computationally investigated using Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDXS), Transmission Electron Microscopy (TEM), and Differential Scanning Calorimetry (DSC) to assess its thermodynamic models and parameters. The Ti-rich region was accurately assessed in this investigation, including multiple phase region boundaries and the identifications of all related phases. Based on the experimental results from this investigation and various literature articles, the thermodynamic description of Ti-Al-Mn in this work is in good agreement with experimental results and can be applied as a basis to develop higher-order multicomponent titanium alloys. Graphical abstract: Highlights: The Ti-rich region in Ti-Al-Mn system was investigated experimentally. Thermodynamic description of Ti-Al-Mn system was reassessed for Ti-rich regions. This thermodynamic work contributes to the commercial titanium alloy database. L12 phase was confirmed and characterized of morphology and lattice parameters.